Three new species of the family Aoridae collected from Sagami Bay, central Japan (Crustacea: Amphipoda) - Ariyama, Hiroyuki; Kohtsuka, Hisanori (Zootaxa, 2022)
Three new species of the amphipod family Aoridae Stebbing, 1899 were collected from the bottom of a 40–400 m depth in Sagami Bay, central Japan. Aora biarticulata sp. nov. is characterized by the accessory flagellum with 2 articles, the weakly setose male gnathopod 1 and the male gnathopod 2 with setose carpus and propodus. Aoroides sagamiensis sp. nov. has a distinctive male gnathopod 1 with poorly setose basis and heavily setose merus. Grandidierella gracilis sp. nov. has stridulating ridges on the carpus of the male gnathopod 1. This new species can be distinguished from its related congeners by the teeth arrangement on the male gnathopod 1 carpus, the poorly setose antennae, the sparsely setose posterior margins of the pereopods 6, 7 bases, and the ordinary form of the male gnathopod 2.